Gut Mycobiome in Patients With Chronic Kidney Disease Was Altered and Associated With Immunological Profiles - Hu, Jialin; Wei, Shichao; Gu, Yifeng; Wang, Yang; Feng, Yangkun; Sheng, Jiayi; Hu, Lei; Gu, Chaoqun; Jiang, Peng; Tian, Yu; Guo, Wei; Lv, Longxian; et al. (Frontiers in Immunology, 2022)
Objectives Mounting evidence suggests that bacterial dysbiosis and immunity disorder are associated with patients with chronic kidney disease (CKD), but the mycobiome is beginning to gain recognition as a fundamental part of our microbiome. We aim to characterize the profile of the mycobiome in the gut of CKD patients and its correlation to serum immunological profiles. Methods and materials Ninety-two CKD patients and sex–age–body mass index (BMI)–matched healthy controls (HCs) were recruited. Fresh samples were collected using sterile containers. ITS transcribed spacer ribosomal RNA gene sequencing was performed on the samples. An immunoturbidimetric test was used to assess the serum levels of immunological features. Results The CKD cohort displayed a different microbial community from that in the HC cohort according to principal coordinate analysis (PCoA). (P=0.001). The comparison of the two cohorts showed that the CKD cohort had significantly higher gut microbial richness and diversity (P<0.05). The CKD cohort had lower abundances of Candida, Bjerkandera, Rhodotorula, and Ganoderma compared to the HC cohort, while it had higher Saccharomyces (P<0.05). However, the microbial community alteration was inconsistent with the severity of kidney damage in patients, as only patients in CKD stage 1~3 had differed microbial community concerning for HCs based on PCoA (P<0.05). The serum concentration of the kappa light chain in CKD patients was positively associated with Saccharomyces, whereas the it was negatively associated with Ganoderma (P<0.05). Conclusions Not only was gut mycobiome dysbiosis observed in CKD patients, but the dysbiosis was also associated with the immunological disorder. These findings suggest that therapeutic strategies targeting gut mycobiome might be effective.